Managing cross-cultural communication : principles and practice - Maude, Barry (New York : Palgrave MacMillan, 2011)
'An accessible and lively introduction to the management of cross-cultural communication for undergraduate and graduate business students. Drawing on the latest research and incorporating the author's own extensive experience of working in different cultural settings, it addresses the core theory and practice. An essential course companion'--
Machine generated contents note: -- PART ONE: PRINCIPLES -- What is Culture? Culture Values in business and society -- Language Matters -- Nonverbal aspects of cross-cultural communication -- Prejudice and Stereotypes -- PART TWO: PRACTICE -- Expatriate performanceCross-cultural adjustmentDeveloping cross-cultural skillsCommunicating across the cultural distanceManaging and working in multicultural teamsCross-cultural meetings and negotiationsCross-cultural interviews and selection.
Includes bibliographical references and index.
Keywords: Intercultural communication; Business communication